2010
DOI: 10.1007/s00401-010-0700-3
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and sub-cellular pathology of animal prion diseases: relationship between morphological changes, accumulation of abnormal prion protein and clinical disease

Abstract: The transmissible spongiform encephalopathies (TSEs) or prion diseases of animals are characterised by CNS spongiform change, gliosis and the accumulation of disease-associated forms of prion protein (PrP(d)). Particularly in ruminant prion diseases, a wide range of morphological types of PrP(d) depositions are found in association with neurons and glia. When light microscopic patterns of PrP(d) accumulations are correlated with sub-cellular structure, intracellular PrP(d) co-localises with lysosomes while non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
108
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(118 citation statements)
references
References 137 publications
8
108
2
Order By: Relevance
“…Surprisingly, the PrP res aggregates in CJD brains that were observed by light microscopy were not detected by EM. Although it seems counterintuitive, this distinction has been reported by others (19). In sharp contrast, PrP res aggregates were not detected in FFI brains by using standard procedures.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Surprisingly, the PrP res aggregates in CJD brains that were observed by light microscopy were not detected by EM. Although it seems counterintuitive, this distinction has been reported by others (19). In sharp contrast, PrP res aggregates were not detected in FFI brains by using standard procedures.…”
Section: Resultsmentioning
confidence: 57%
“…2B). In humans, spongiosis is a rare feature that distinguishes most of the prion diseases, including CJD but not FFI, from other neurodegenerative diseases (19). Other notable differences between the mice also characteristically distinguish CJD and FFI diseases in humans.…”
Section: Resultsmentioning
confidence: 99%
“…In prion-infected tissues, PrPSc aggregates may be membrane-associated, either on the cell surface or within intracellular vesicles, or may be deposited in the form of amyloid plaques in the extracellular space (11,14,15). "Amyloid" refers to an ordered fibrillar structure in which hydrogen-bonded ␤-sheets are oriented perpendicular to the fibril axis, forming an architecture known as cross-␤ (16).…”
mentioning
confidence: 99%
“…43 and 44; reviewed in Ref. 15). This technique has also revealed that membrane-bound PrPSc gives rise to unusual membrane lesions, in particular plasma membrane invaginations on neurons and astrocytes (15,45,46).…”
mentioning
confidence: 99%
See 1 more Smart Citation